2020
DOI: 10.1093/ajhp/zxaa176
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives from the frontline: A pharmacy department’s response to the COVID-19 pandemic

Abstract: Purpose The global coronavirus 2019 (COVID-19) pandemic has created unprecedented strains on healthcare systems around the world. Challenges surrounding an overwhelming influx of patients with COVID-19 and changes in care dynamics prompt the need for care models and processes that optimize care in this medically complex patient population. The purpose of this report is to describe our institution’s strategy to deploy pharmacy resources and standardize pharmacy processes to optimize the manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 27 publications
2
45
1
Order By: Relevance
“…Despite increased work responsibilities and work reassignments, pharmacists helped monitor COVID-19 medication use and adverse effects, helped manage drug shortages and supply chain issues, worked to preserve PPE, helped establish temporary COVID-19 hospitals during surges, wrote treatment guidelines, and provided education to clinicians and the public. 17,19,36 Collins et al 37 highlighted the importance of pharmacy care in their retrospective review of 197 patients with COVID-19 who had at least 1 pharmacist intervention during their hospital stay. These 197 patients had 15,818 medication days and received 1,572 pharmacist interventions (mean medication interventions per patient 8).…”
Section: Impact Of Asps On the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increased work responsibilities and work reassignments, pharmacists helped monitor COVID-19 medication use and adverse effects, helped manage drug shortages and supply chain issues, worked to preserve PPE, helped establish temporary COVID-19 hospitals during surges, wrote treatment guidelines, and provided education to clinicians and the public. 17,19,36 Collins et al 37 highlighted the importance of pharmacy care in their retrospective review of 197 patients with COVID-19 who had at least 1 pharmacist intervention during their hospital stay. These 197 patients had 15,818 medication days and received 1,572 pharmacist interventions (mean medication interventions per patient 8).…”
Section: Impact Of Asps On the Covid-19 Pandemicmentioning
confidence: 99%
“…Of these interventions, the most common were regimen simplification and medication timing to minimize the frequency of hospital staff room entry while caring for infected patients, followed by stewardship interventions to ensure optimal use of antimicrobials. 37 More recently, with the authorization of new oral COVID-19 antiviral medications like ritonavir-boosted nirmatrelvir, pharmacists have again been of great importance in counseling, performing medication reconciliation, and mitigating potentially severe drug-drug interactions. 38…”
Section: Impact Of Asps On the Covid-19 Pandemicmentioning
confidence: 99%
“…Pharmacy societies and organizations have provided numerous COVID‐19 educational resources. (Table 1) To date, pharmacists from China, Australia, Malaysia, Saudi Arabia, and the United States (US) have described a variety of roles and contributions from pharmacists during the COVID‐19 pandemic 3‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Hospital pharmacists are evaluating emerging COVID‐19 drug therapy options to rapidly make patient care decisions, monitoring and adjusting COVID‐19 medications to prevent adverse side effects, managing numerous drug shortages, maintaining uninterrupted drug supply, resolving supply chain issues for critical care medicines, adjusting workflow to preserve personal protective equipment, and establishing new pharmacy services in temporary emergency COVID‐19 hospitals. Experience from one U.S. hospital identified that COVID‐19 patients received an average of 19.8 different medications and pharmacists made an average of eight interventions per patient 6 . A panel of U.S. physicians and six clinical pharmacists co‐authored the National Institute of Health (NIH) treatment guidelines for COVID‐19 intended for frontline health care providers caring for patients during the rapidly evolving pandemic 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation